Application of Principles of Projectised and Nonprojectised Organisations: A Micro Level Approach to Construction Procurement Systems - Chong, Heap Yih (Universal Publishers, 2013)
Many procurement systems have been developed for managing construction projects. None of the previous studies emphasize on the subsequent managerial approach to be adopted toward the selected procurement system. Further managerial theories are required to enhance their performance and effectiveness. Thus, this study aims to promote and integrate the principles of projectised and nonprojectised organisations, in the context of selected procurement systems and, subsequently, develops an appropriate combination based on literature review. It focuses on the micro or project level of organisational principles to improve the management strategies of different procurement systems. The results show that the principles are complementary to procurement systems and provide a useful insight into the theories for integration of organisational principles and procurement systems in terms of project-management knowledge.